Combined Use of Mycobacterium tuberculosis–Specific CD4 and CD8 T-Cell Responses Is a Powerful Diagnostic Tool of Active Tuberculosis. (31st October 2014) - Rozot, Virginie; Patrizia, Amelio; Vigano, Selena; Mazza-Stalder, Jesica; Idrizi, Elita; Day, Cheryl L.; Perreau, Matthieu; Lazor-Blanchet, Catherine; Ohmiti, Khalid; Goletti, Delia; Bart, Pierre-Alexandre; Hanekom, Willem; et al.
Abstract: Immune-based assays are promising tools to help to formulate diagnosis of active tuberculosis. A multiparameter flow cytometry assay assessing T-cell responses specific to Mycobacterium tuberculosis and the combination of both CD4 and CD8 T-cell responses accurately discriminated between active tuberculosis and latent infection.